2022
DOI: 10.1111/ejh.13818
|View full text |Cite
|
Sign up to set email alerts
|

Early report on the severity of COVID‐19 in hematologic patients infected with the SARS‐CoV2 omicron variant

Abstract: Introduction Patients with hematologic disease are at high risk of morbidity and mortality from COVID‐19 due to disease‐inherent and therapy‐related immunodeficiency. Whether infection with the SARS‐CoV2 omicron variant leads to attenuated disease severity in these patients is currently unknown. Methods We assessed clinical and laboratory parameters in 61 patients with underlying hematologic conditions with a SARS‐CoV2 omicron variant infection confirmed by nucleic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…At the beginning of the year 2022, the Omicron variant became the predominant cause of the disease [ 130 ]. Infection with the Omicron variant caused milder disease with much fewer need for hospitalization [ 131 , 132 ]. There were less frequent lower respiratory tract infections caused by the Omicron variant and thus less frequent severe forms of the disease were observed [ 133 ].…”
Section: Continuing Mutation Of Sars-cov-2mentioning
confidence: 99%
“…At the beginning of the year 2022, the Omicron variant became the predominant cause of the disease [ 130 ]. Infection with the Omicron variant caused milder disease with much fewer need for hospitalization [ 131 , 132 ]. There were less frequent lower respiratory tract infections caused by the Omicron variant and thus less frequent severe forms of the disease were observed [ 133 ].…”
Section: Continuing Mutation Of Sars-cov-2mentioning
confidence: 99%
“…While some studies indicate that a previous SARS-CoV-2 infection may reduce the likelihood of olfactory dysfunction in a subsequent COVID infection [51], it is known that a previous COVID infection with an earlier variant does not necessarily prevent a second loss of smell when the same individual subsequently becomes infected with a different SARS-CoV-2 variant [134,135]. It also does not seem that vaccinations reliably prevent the occurrence of loss of smell in break-through infections [9,52,88,136].…”
Section: Discussionmentioning
confidence: 99%
“…2). Twenty-two studies were from populations primarily of European ancestry [8,32,[40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59], eight studies on East Asians [60][61][62][63][64][65][66][67], three studies on South Asians [68][69][70], three studies on Latinos [71][72][73], four studies on populations in Africa [74][75][76][77], and one study from West Asia (Turkey [78]). The location of studies, with the prevalence indicated by the color intensity, and the cohort size indicated by the size of the circles, shows that Western countries report the highest prevalence, while studies from East Asia and Africa report the lowest prevalence (Fig.…”
Section: Properties Of Studiesmentioning
confidence: 99%
“…By February 2023, more than 750 million SARS-CoV2 infections and 6.8 million COVID-19 associated deaths had been reported globally [1]. The development of vaccines against SARS-CoV2, which primarily protect against severe disease, has however greatly reduced both COVID-19-related mortality and morbidity [2,3]. Global vaccination programmes were fast-tracked under the COVID-19 Vaccines Global Access (COVAX) initiative at the beginning of 2021 [4].…”
Section: Introductionmentioning
confidence: 99%